Adaptation Strategies of the Colombian Hotel Industry During the Pandemic - López Cadavid, Diego Alejandro; Restrepo Morales, Jorge Aníbal; Vanegas López, Juan Gabriel; Arango Mesa, Maria Alexandra (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Different aspects related to business dynamics motivate the design and execution of strategies. In the case of the Colombian hospitality industry, the recent price regulation, the emergence of disruptive technologies, and events affecting public health demonstrate the need to outline appropriate tactics that lead to an adequate contextualized implementation. This study proposes an Analytic Hierarchy Process (AHP) model to evaluate the set of tactics and strategies most applicable to these current situation alternatives faced by hoteliers in the city of Medellin. The results of the evaluation indicate that intensive, generic business and defensive strategies are the most preferred. In addition, as expected, the results suggest that the pandemic has the greatest weight and should therefore be selected by hotel companies as the priority alternative on which to focus their strategies.